Evaluation of the village development index as an effort to provide the right policy intervention - Muhammad Roisul Basyar; Anggraeny Puspaningtyas; Vivtania Salsa Bella; Dimas Kurnia Firmansyah (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2022)
The change in the paradigm of village development from "building villages" to "developing village" forced the village government to provide the right policies so that the expected development could be realized. However, the data that has so far been associated with the developing village index is quantitative and tends to be stagnant. This study aims to evaluate the village development index qualitatively. By using a comparative program after only evaluation approach and a qualitative descriptive research method that emphasizes how the community and village government interpret the programs that have been given before. The results of the study show different findings from the quantitative approach, especially on the Economic Resilience index, which seems to be no different from other villages in general in Indonesia. Even though it has the ideal potential to become an independent village. The recommendations resulting from this research are that it is necessary to maximize Access to Financial Institutions and Trade Service Centers so that their potential can be developed towards an independent village.